The Role of Team Diversity, Managerial Transparency, and Continuous Learning in Enhancing the Creativity of Social Service Employees of Kerinci Regency - Fitriani; Sumiati (SAFE-Network, 2026)
This study aims to analyze the influence of team diversity, managerial transparency, and continuous learning on employee creativity at the Kerinci Regency Social Service. The study used a quantitative approach with a survey method with a sample of 62 employees. Data were collected through a questionnaire that had been tested for validity and reliability, then analyzed using multiple linear regression with IBM SPSS version 26.0. The results showed that team diversity, managerial transparency, and continuous learning partially had a positive and significant effect on employee creativity. A simultaneous test also proved that these three independent variables collectively had a significant influence on employee creativity. The coefficient of determination of 0.797 indicates that 79.7% of the variation in employee creativity can be explained by these three variables, while the remaining 20.3% is influenced by factors outside the research model. Thus, increasing team diversity, managerial transparency, and continuous learning are important factors in fostering employee creativity at the Kerinci Regency Social Service.